2001
DOI: 10.1055/s-2001-14069
|View full text |Cite
|
Sign up to set email alerts
|

Is Factor XII Deficiency Related to Recurrent Miscarriage?

Abstract: Factor XII (FXII) is an important protease that plays a major role in the initiation of the intrinsic pathway of blood coagulation. Although congenital FXII deficiency is not associated with a clinical bleeding tendency, it can be identified on a routine coagulation test, such as a prolonged activated partial thromboplastin time. This deficiency is a rare autosomal recessive disorder. It is still unclear whether FXII deficiency causes any disorders during pregnancy. Recurrent miscarriages and placental abrupti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 18 publications
(20 reference statements)
1
22
1
3
Order By: Relevance
“…None of our patients showed any undue bleeding at delivery. The same was true for other reports [30]. Five of the propositae have taken oral contraception and no thrombosis has been reported.…”
Section: Discussionsupporting
confidence: 72%
“…None of our patients showed any undue bleeding at delivery. The same was true for other reports [30]. Five of the propositae have taken oral contraception and no thrombosis has been reported.…”
Section: Discussionsupporting
confidence: 72%
“…Yamada et al also found an increased, but low, prevalence of 2.9% for FXII deficiency in 241 RPL patients [64]. Such low numbers might partly explain conflicting results; indeed, a very recent report suggested no role for FXII deficiency in recurrent miscarriage [65]. Detailed studies of FXII at the molecular level are essential for determining its developmental functions during pregnancy.…”
Section: Introductionmentioning
confidence: 94%
“…Gallimore et al 16 reported a high incidence (20.9%) of FXII deficiency in patients who were lupus anticoagulant (LA) positive. 18 Recently, Pauer et al 19 generated mice deficient in FXII using a gene-targeting approach. They studied plasma samples from LA positive patients for the presence of anti-FXII and reported that many patients were positive for anti-FXII detected by ELISA and surface plasmon resonance.…”
Section: Introductionmentioning
confidence: 99%